2017
DOI: 10.1007/s10433-017-0434-3
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functioning is more closely related to real-life mobility than to laboratory-based mobility parameters

Abstract: Increasing evidence indicates that mobility depends on cognitive resources, but the exact relationships between various cognitive functions and different mobility parameters still need to be investigated. This study examines the hypothesis that cognitive functioning is more closely related to real-life mobility performance than to mobility capacity as measured with standardized laboratory tests. The final sample used for analysis consisted of 66 older adults (72.3 ± 5.6 years). Cognition was assessed by measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…These gait based temporal elements are likely to consist of the same physiological construct, indeed the correlation between these two iTUG variables was 0.85 suggesting the measures were highly related. Cognition and total TUG time has been previously investigated, demonstrating that those with lower levels of cognition, perform the TUG more slowly in older people with Parkinson's disease or those with mild-moderate cognitive impairment 28,36,44,45 . The findings of the current study suggest that it is only the duration of walking phases, not turning or sit to stand, that are correlated with cognitive function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These gait based temporal elements are likely to consist of the same physiological construct, indeed the correlation between these two iTUG variables was 0.85 suggesting the measures were highly related. Cognition and total TUG time has been previously investigated, demonstrating that those with lower levels of cognition, perform the TUG more slowly in older people with Parkinson's disease or those with mild-moderate cognitive impairment 28,36,44,45 . The findings of the current study suggest that it is only the duration of walking phases, not turning or sit to stand, that are correlated with cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations were observed in individuals with mild cognitive impairment and the performance of the sub-phases of the iTUG 25,28 . These studies suggested cognitive function correlated with sit-tostand transition, and turning sub-phases along with some metrics of gait 25,28 . FoF, which has been linked to risk of falling and has been shown to correlate to subphases of the iTUG [29][30][31] , however these studies have only investigated individuals with Parkinson's disease.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Another study in 279 functionally and cognitively independent older people in retirement communities found an average wear time of 13.6 h/day (SD 1.3) [ 37 ]. The ‘Mobility Study’, which recruited older people to wear GPS trackers for 1 week had to exclude 15 of 86 participants due to missing sensor data [ 42 ]. Lastly, Liddle et al [ 38 ] reported problems with GPS measurement accuracy within the home environment.…”
Section: Novel Methods To Assess Lsmmentioning
confidence: 99%
“…In light of current demographic changes, it is important to study factors contributing to an active, independent and healthy lifestyle up to and into old age. An increasing number of studies have investigated the manifold relations between mobility and physical as well as psychological health, especially in older adults (Giannouli, Bock, & Zijlstra, 2018;Kaspar, Oswald, Wahl, Voss, & Wettstein, 2015;Rantakokko et al, 2015). However, most studies that found significant relations between mobility and health outcomes focus on the physical dimension of mobility (how much activity takes place) and less on its spatial dimension (where activity takes place).…”
Section: Introductionmentioning
confidence: 99%